Guppy Fish (Poecilia reticulata) Behavior and Growth Are Affected by Variations in Light Color - Ainanur Fauziyah Almaas; Harlita Harlita (Jurnal Perikanan Universitas Gadjah Mada, 2023)
This study aims to determine the effect of different colors of light on the behavior and growth of guppy fish (Poecilia reticulata). This research was conducted experimentally using a completely randomized design (CRD) with four treatments and five replications. The treatment used was treatment A with a white light color, treatment B with a red light color, treatment C with a yellow light color, and treatment D with a blue light color. The parameters observed were growth in absolute weight, fish behavior, and water quality (temperature and pH). Data analysis with One Way Anova and further test with LSD using SPSS 25. Based on the statistical hypothesis test with One Way ANOVA showed F count (3.828) > F table (3.24) 5% level for guppy fish growth parameters so that the results are the effect of different light colors on the growth of guppy fish in each treatment. Fish behavior in all treatments gave a positive phototaxis response. The quality of the water in the experimental medium was within acceptable limits for guppy fish cultivation, 26-28°C for water temperature and 7 for the degree of acidity (pH) of water.